Al-Hajj, Abdul Rahman. “The Establishment of Uṣūl al-Tafsīr (Principles of Exegesis) and its Relevance to Uṣūlī Theory,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 53-80. - الحاج عبدالرحمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2004)
Abdul Rahman al-Hajj’s article aims to address the void that exists in establishing rules for the science of uṣūl al-tafsīr (principles of Qur’anic exegesis), doing so by examining the history of establishing rules for uṣūl and understanding the historical reasons which led to this void. He argues that the science of uṣūl al-fiqh (principles of jurisprudence) is the most qualified science to inform the basis for the formation of the science of uṣūl al-tafsīr. Al-Hajj surveys the studies that attempted to adopt uṣūl al-fiqh as a foundation for the science of tafsīr and offers a comparison of uṣūl al-fiqh to the science of grammar. He argues for the need to invest in all fields relevant to ascertaining evidence and for ta’wīl (hermeneutic interpretation) in modern Arabic studies and its traditional sciences. Moreover, he believes in the importance of modern linguistic studies and the methodologies of literary criticism in the development of research on tafsīr, and emphasizes that the Qur’anic text is a functional sacred text.